Transient DNMT3L Expression Reinforces Chromatin Surveillance to Halt Senescence Progression in Mouse Embryonic Fibroblast - Yu, Yoyo Chih-Yun; Hui, Tony ZK; Kao, Tzu-Hao; Liao, Hung-Fu; Yang, Chih-Yi; Hou, Chia-Chun; Hsieh, Hsin-Ting; Chang, Jen-Yun; Tsai, Yi-Tzang; Pinskaya, Marina; Yang, Kai-Chien; Chen, Yet-Ran; et al. (Frontiers in Cell and Developmental Biology, 2020)
Global heterochromatin reduction, one of the hallmarks of senescent cells, is associated with reduced transposable element repression and increased risk of chromatin instability. To ensure genomic integrity, the irreparable cells in a population exit permanently from the cell cycle, and this process is termed “senescence”. However, senescence only blocks the expansion of unwanted cells, and the aberrant chromatin of senescent cells remains unstable. Serendipitously, we found that the transient ectopic expression of a repressive epigenetic modulator, DNA methyltransferase 3-like (DNMT3L) was sufficient to delay the premature senescence progression of late-passage mouse embryonic fibroblasts (MEFs) associated with a tightened global chromatin structure. DNMT3L induces more repressive H3K9 methylation on endogenous retroviruses and downregulates the derepressed transposons in aging MEFs. In addition, we found that a pulse of ectopic DNMT3L resulted in the reestablishment of H3K27me3 on polycomb repressive complex 2 (PRC2)-target genes that were derepressed in old MEFs. We demonstrated that ectopic DNMT3L interacted with PRC2 in MEFs. Our data also suggested that ectopic DNMT3L might guide PRC2 to redress deregulated chromatin regions in aging cells. This study might lead to an epigenetic reinforcement strategy for overcoming aging-associated epimutation and senescence.